Function allocation theory for creative design - Tomiyama, Tetsuo (Elsevier, 2016)
Function structure influences on systems architecture (or product architecture). This paper discusses a design method for creative design solutions that focuses on the allocation of functions. It first proposes a theory called “Function Allocation Theory” to allocate a function to an appropriate subsystem or component during the systems decomposition phase. By doing so, the complexity of design solutions can be reduced. The theory is applied to some examples including collaborative robots and robotics maintenance. Finally, the paper illustrates a case study of designing a reaction-free fastening system using this theory.
Keywords: Function; modelling; architecting